Clothing burns in Canadian children - Stanwick, Richard S. (1985)
A Canadian survey of 11 tertiary care pediatric centres with specialized burn facilities revealed that an estimated 37 children up to 9 years of age are admitted annually to such hospitals because of clothing burns. Sleepwear accounts for an estimated 21 such burns per year. Girls were found to suffer the most severe burns and represented eight of the nine children in the series who died. Loose and flowing garments dominated the girls' styles. The results of multiple-regression analysis confirmed that style of clothing (loose and flowing as opposed to snug) was the most significant predictor of burn severity, length of hospital stay, the need for skin grafting and survival. The ignition situation (avoidance of parental supervision at the time of injury) was the only other important predictor. The success of regulatory actions in other countries in reducing the incidence of severe clothing burns is reviewed, and preventive strategies for Canada are explored.